A novel single metal layer MEMS-based step-down transformer. (November 2016) - Khan, F.; Zhu, Y.; Lu, J.; Pal, J.
Abstract: This paper presents for the first time single metal layer step-down on-chip transformer. The design is characterized for VHF and UHF frequency ranges. The prototype is coreless (air core), which is suitable for high frequency operations. The design is fabricated in a standard Metal-MUMPs fabrication process, which offers a single structure layer. The primary inductance of 10.7 nH and the transformer quality factor of 8.8 have been achieved at 1 GHz. The coupling coefficient is 0.60 and the efficiency is 76% with matched load at 1 GHz. The total footprint area of micro-transformer is 0.49 mm 2 .